Genetic polymorphisms in inflammatory genes and pancreatic cancer risk: a two-phase study on more than 14 000 individuals. (21st November 2019) - Gentiluomo, Manuel; Peduzzi, Giulia; Lu, Ye; Campa, Daniele; Canzian, Federico
Abstract: There is overwhelming evidence that inflammation plays a key role in the pathogenesis of cancer and its progression. Inflammation is regulated through a complex network of genes and polymorphic variants in these genes have been found to be associated to risk of various human cancers, alone or in combination with environmental variables. Despite this, not much is known on the genetic variability of genes that regulate inflammation and risk of pancreatic ductal adenocarcinoma (PDAC). We performed a two-phase association study considering the genetic variability of 76 genes that are key players in inflammatory response. We analysed tagging single nucleotide polymorphisms (SNPs) and regulatory SNPs on 7207 PDAC cases and 7063 controls and observed several associations with PDAC risk. The most significant association was between the carriers of the A allele of the CCL4 -rs1719217 polymorphism, which was reported to be also associated with the expression level of the CCL4 gene, and increased risk of developing PDAC (odds ratio = 1.12, 95% confidence interval = 1.06–1.18, P = 3.34 × 10 −5 ). This association was significant also after correction for multiple testing, highlighting the importance of using potentially functional SNPs in order to discover more genetic variants associated with PDAC risk.